SYSTEM AND METHOD FOR JOINT DEGRADATION ESTIMATION AND IMAGE RECONSTRUCTION IN MAGNETIC RESONANCE IMAGING - EL FAKHRI, GEORGES; MEYER, FRANCOIS, GEORGE; DAGHER, JOSEPH (2013)
A magnetic resonance imaging (MRT) method for jointly estimating an image degradation and reconstructing an image of a subject in which that image degradation is mitigated is provided. The MRI system is operated to acquire multiple different k-space data sets that are acquired with different acquisition parameters so as to modulate the image degradation to be estimated. Using an iterative process, the image degradation is estimated while jointly reconstructing an image in which the estimated image degradation is mitigated. La présente invention concerne un procédé d'imagerie par résonance magnétique (IRM) permettant d'effectuer conjointement l'estimation d'un affaiblissement d'image et la reconstruction d'une image d'un sujet dont l'affaiblissement est atténué. Le système IRM acquiert plusieurs ensembles différents de données d'espace k qui sont acquis avec différents paramètres d'acquisition afin de moduler l'affaiblissement d'image à estimer. Au moyen d'un processus itératif, l'affaiblissement d'image est estimé tout en reconstruisant conjointement une image dont l'affaiblissement d'image est atténué.